2019
DOI: 10.1002/tafs.10166
|View full text |Cite
|
Sign up to set email alerts
|

Using Multistage Design‐Based Methods to Construct Abundance Indices and Uncertainty Measures for Delta Smelt

Abstract: Population abundance indices and estimates of uncertainty are starting points for many scientific endeavors. However, if the indices are based on data collected by different monitoring programs with possibly different sampling procedures and efficiencies, applying consistent methodology for calculating them can be complicated. Ideally, the methodology will provide indices and associated measures of uncertainty that account for the sample design, the level of sampling effort (e.g., sample size), and the capture… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

3
38
0

Year Published

2019
2019
2024
2024

Publication Types

Select...
8

Relationship

3
5

Authors

Journals

citations
Cited by 20 publications
(41 citation statements)
references
References 26 publications
3
38
0
Order By: Relevance
“…It seems unlikely that the level of population declines and recoveries observed in the SFE would be predominantly driven by gear avoidance (Tobias 2020). The overall patterns seen in this study are generally consistent with those observed in larval fish surveys where swimming capabilities of fishes would be of less concern (Dege and Brown 2004), other sampling methods that we expect to be unaffected by turbidity (Grimaldo et al 2009), and with studies that have adjusted for fish catchability (Mahardja et al 2017b, Peterson and Barajas 2018, Polansky et al 2019).…”
Section: Discussionsupporting
confidence: 86%
See 1 more Smart Citation
“…It seems unlikely that the level of population declines and recoveries observed in the SFE would be predominantly driven by gear avoidance (Tobias 2020). The overall patterns seen in this study are generally consistent with those observed in larval fish surveys where swimming capabilities of fishes would be of less concern (Dege and Brown 2004), other sampling methods that we expect to be unaffected by turbidity (Grimaldo et al 2009), and with studies that have adjusted for fish catchability (Mahardja et al 2017b, Peterson and Barajas 2018, Polansky et al 2019).…”
Section: Discussionsupporting
confidence: 86%
“…In addition, spawning for some species (e.g., Sacramento sucker, striped bass, American shad) occur in upstream tributaries not sampled in our study area and a portion of their young‐of‐year may continue to rear in these upstream areas (Moyle 2002). The imperfect spatial coverage of our data may bias our resistance and resiliency estimates to some extent; however, most of the juvenile fishes we analyzed either migrate through or occur largely within our study area, and the patterns described in our study are consistent with large‐scale changes in the populations of these fish species documented by other monitoring programs (Brown and Michniuk 2007, Feyrer et al 2015, Polansky et al 2019). Last, our analysis did not account for catchability or detection probability, which can often vary considerably over time and space (MacKenzie et al 2002).…”
Section: Discussionsupporting
confidence: 63%
“…Different choices of the conditional distribution for truen̂s,tfalse|ns,t can be made, which in turn can affect inference (Knape et al ., 2011). We chose a lognormal distribution because it ensures strictly positive abundance indices (especially useful when abundance indices are near zero), it is perhaps the most common assumption (although more often in terms of a normal distribution when working with log abundances), and because earlier work (Polansky et al ., 2019) suggests it is to be preferred over a normal distribution for the case study model described in Section 5.…”
Section: Model Descriptionmentioning
confidence: 99%
“…Delta Smelt were considered to have been abundant until the early 1980s, when relatively large and prolonged declines in available abundance indices were first observed (Moyle et al 1992;2016). Delta Smelt abundance indices declined abruptly again in the early 2000s; the latter resulting in a nearly continual decline to its contemporary nearly extirpated status (Thomson et al 2010;Polansky et al 2019).…”
Section: Did a Shifting Ecological Baseline Mask The Predatory Effectmentioning
confidence: 99%